Penyuluhan Pendidikan Pengetahuan Gaya Hidup Merdeka dari Hipertensi (P3LSM) di Desa Beka, Kab. Sigi Sulawesi Tengah - Bayu Eka Kurniawan; Ismunandar Wahyu Kindang; Basri; Sringati (LPPM Universitas Widya Nusantara, 2025)
Hypertension is a condition in which a person's blood pressure is ≥140 mmHg (systolic) and/or ≥ 90 mmHg (diastolic). Hypertension is called the silent killer because treatment is often too late. Management of hypertension includes non-pharmacological therapy and pharmacological therapy. Non-pharmacological therapy in the form of lifestyle modification includes dietary patterns, physical activity, smoking bans and alcohol consumption restrictions. This study uses a type of quantitative research using a one-group pre-test post-test design to design a pre-exprimental research. The results of the study showed that before the provision of education, the majority of respondents were in the category of lack of knowledge level, while after the provision of education, the majority of respondents were in the category of good knowledge level.